(untitled) (Baghdad Science Journal, 2022)
The infection with H. Pylori stimulates a signaling cascade that causes the generation of Cytokines and provokes Oxidative stress that is involved in the chronic inflammatory response leads to Gastric cancers. Reactive oxygen species (ROS) produce 8-Hydroxydeoxyguanosine (8-OHdG), the persistent oxidative DNA damage product. The study objective was to assess if there was a link between inflammatory cytokine levels and the presence of Oxidative DNA damage in Gastric tumor patients. In addition, evaluation of the diagnostic and prognostic value of Oxidative DNA damage and inflammatory cytokine biomarkers for Stomach cancers is being conducted. The study was accomplished on medically diagnosed Stomach cancer patients before any form of treatment. A total of 33 patients with Gastric cancers were selected and divided into Stages I, II, and III according to clinical pathology, and 32 age-matched healthy subjects as a control group. The Serum 8-OHdG, IL-6, TNF-α, IFN-γ & CEA were evaluated. The results revealed a highly significant rise (P<0.0001) in blood levels of 8-OHdG, TNF-α, & IFN-γ, and a non-significant (P=0.4747) increasing in IL-6 in GC patients compared to Controls, with levels gradually increasing as disease stages progressed. Furthermore, in GC patients, there was an insignificant (P=0.3472) positive correlation (r=0.1292) among 8-OHdG, IL-6, and CEA levels, but a noteworthy (P<0.0001) positive correlation (r=0.7235) among 8-OHdG, TNF-α, and CEA levels. In GC patients, however, there was an insignificant (P=0.6342) negative correlation (r=-0.06559) among 8-OHdG, IFN-γ, and CEA levels. The results of the current study show a strong link between serum levels of the 8-OHdG as well as inflammatory cytokines in GC patients. The significant enhancement in oxidative DNA damage, as well as overexpression of inflammatory cytokine biomarkers and CEA in the blood suggests that Oxidative stress and chronic inflammation are included in GC carcinogenesis. These observations suggest that 8-OHdG, TNF-α, & IFN-γ are viable biomarkers for the Gastric tumor prediction.